Yield Analysis and Phytochemical Screening of Ethanol Extract of Phaleria macrocarpa Leaves - Ira Cinta Lestari; Dharma Lindarto; Syafruddin Ilyas; Tri Widyawati; Suryani Eka Mustika (Universitas Muhammadiyah Sumatera Utara, 2023)
Phaleria macrocarpa leaves have the potential to be used as raw materials for medicines derived from natural ingredients, but research is needed to determine the content and efficacy of these plants. This study aims to analyze the yield and screening of the content of phytochemical compounds in the ethanolic extract of the Phaleria macrocarpa leaves. This research is a descriptive study. Extract yield analysis was performed by calculating the weight ratio of the extract divided by the simplicia multiplied by one hundred percent. Screening for the phytochemical content was carried out for compounds belonging to the class of flavonoids, saponins, tannins, alkaloids, steroids, and triterpenoids. The results of the calculation of the yield of the extract obtained were 14.58% and the results of the phytochemical test showed that the extract contained flavonoids, alkaloids, tannins, glycosides, saponins, and steroids.